2020
DOI: 10.1088/1742-6596/1663/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Uno stacko based on realistic mathematics: A developing learning media of trigonometry

Abstract: This research aimed to develop a media uno stacko mathematics based on a realistic mathematical approach to improve students’ understanding of mathematical concepts. The development model used was ADDIE with the pretest and posttest research designs in the control and experimental classes. The instruments used in this study were documentation, tests, and questionnaires. The analysis showed that students have problems in understanding the concepts and need engaging learning media. Then we think to design a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The response of students from SDN 2 Sidowarno to the instructional media on Newton's laws of motion can be seen in Table 6 as follows: Based on the validation results and assessment responses, it can be concluded that the Javanese character instructional media based on the Uno Stacko game is highly suitable for implementation. This conclusion is supported by previous research conducted by Kusumaningsih, Buchori, & Cahyono (2020), Nadiya, Aswarliansyah, &Valen (2022), andSuraiya, Amiruddin, Razak, &Pertiwi (2021). These studies have shown that instructional media based on the Uno Stacko game is effective and capable of enhancing students' understanding.…”
Section: Students' Responsesupporting
confidence: 88%
“…The response of students from SDN 2 Sidowarno to the instructional media on Newton's laws of motion can be seen in Table 6 as follows: Based on the validation results and assessment responses, it can be concluded that the Javanese character instructional media based on the Uno Stacko game is highly suitable for implementation. This conclusion is supported by previous research conducted by Kusumaningsih, Buchori, & Cahyono (2020), Nadiya, Aswarliansyah, &Valen (2022), andSuraiya, Amiruddin, Razak, &Pertiwi (2021). These studies have shown that instructional media based on the Uno Stacko game is effective and capable of enhancing students' understanding.…”
Section: Students' Responsesupporting
confidence: 88%
“…The development stage begins with identifying problems, one way to provide diagnostic tests to students. It is in line with the Huda et al (2020); Kusumaningsih et al(2020), which states that before the development of media, first conducted initial tests so that the student's abilities could be known. The study results showed that the numeracy ability of students is still low; this is in line with Megawati and Sutarto (2021); Saefurohman et al (2021).…”
Section: Preliminary Researchmentioning
confidence: 85%
“…Conversely, attracting and retaining skilled workers is one of an organization's greatest achievements. As a means of realizing the organization's mission, Employee's satisfaction and joy in their job, their readiness to work more, and their loyalty to the organization are all considered positive signs of organizational commitment (Meyer et al, 1993;Kusumaningsih et al, 2020;Yuwono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%